Academic Stress and Spiritual Well-Being in Riau - Wiwied Widiyanti; Juntika Nurihsan; Syamsu Yusuf LN; Nandang Budiman; Hendriadi Hendriadi (STAI Hubbulwathan Duri, 2021)
The purpose of this study was to develop a profile of spiritual well-being and academic stress among students in high schools and universities and determine whether there is a relationship between academic stress and spiritual well-being among students in the Indragiri Hulu district of the province of Riau, Indonesia. The quantitative technique is used in this investigation. It was decided to employ a survey design for this investigation. 105 students were chosen to participate in the survey, with an 81 per cent response rate (n = 85). Academic stress was reported by 82 per cent of those who answered the survey questions (70 people). Additionally, according to the findings of this study, women suffer more stress than males, and students in college experience more stress than students in high school. Academic stress, on the other hand, is not significantly associated with gender or educational level. In contrast, the spiritual well-being of students is associated with just a slight link with the academic stress experienced by students.